Analisis Karakteristik Tanah Dasar pada Ruas Jalan Maduran Kabupaten Lamongan Berdasarkan Uji CBR dan Direct Shear - Prima Eko Agustyawan; Rio Rahma Dhana (Jurnal Talenta Sipil, 2026)
Road damage on several road sections in Lamongan Regency may be influenced by unstable subgrade conditions, particularly in areas with high water content and clayey soil characteristics. Subgrade soil with high plasticity and low bearing capacity can reduce pavement performance; therefore, laboratory testing is required to evaluate its physical and mechanical properties. This study aims to analyze the characteristics of subgrade soil on the Maduran road section in Lamongan Regency based on water content, Atterberg limits, California Bearing Ratio (CBR), and direct shear parameters. Soil samples were collected from the study location and tested in the laboratory to determine the physical and mechanical properties of the subgrade. The test results showed a water content of 16.66%, liquid limit of 35.82%, plastic limit of 1.21%, plasticity index of 34.61%, CBR value of 6.80%, shear strength of 0.72 kg/cm², internal friction angle of 15.03°, and cohesion of 0.0340 kg/cm². Based on the plasticity index, the soil is classified as high-plasticity clay, while the CBR value falls into the poor to fair category for subgrade material. Therefore, drainage improvement, proper compaction, and subgrade stabilization are recommended before pavement rehabilitation is carried out.